Back to the Wild - Patent, Dorothy Hinshaw (San Diego Harcourt Brace & Compnay)
Describes efforts to save endangered animals from extinction by breeding them in captivity, teaching them survival skills, and then releasing them into the wild.
Include Color Illustrations and Index.
Keywords: Wildlife reintroduction -- Captive wild animals--Breeding -- Endangered species -- Elephants -- Human-animal relationships -- Welsh language